2017
DOI: 10.1248/cpb.c17-00135
|View full text |Cite
|
Sign up to set email alerts
|

Concise and Versatile Synthesis of Sulfoquinovosyl Acyl Glycerol Derivatives for Biological Applications

Abstract: Sulfoquinovosyl acylpropanediol (SQAP), a chemically modified analogue of sulfoquinovosyl acylglycerol (SQAG) that occurs in sea algae, has been reported to show a variety of biological activities, including accumulation in tumor cells and the inhibition of tumor cell growth. We report herein on a new concise and versatile synthesis of SQAP itself and derivatives bearing iodoaryl groups and boronclusters. This method should be useful for the design and synthesis of SQAG/SQAP derivatives for diagnosis and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The sulfoquinovosyl acylpropanediol (SQAP) 25a and 25b, the chemically modified analogs of sulfoquinovosyl acylglycerol (SQAG) present in sea algae, have been synthesized and it has been observed that they selectively accumulate in tumor cells and prevent the development of tumor cell. 63 Alternative to classical carbohydrate was recently reported by Zelenetskii. This is a complex among polysaccharide hyaluronic acid (HA) and polyborate with the most biochemically adaptive and aqueous-stable structure of 26.…”
Section: Boronated Carbohydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfoquinovosyl acylpropanediol (SQAP) 25a and 25b, the chemically modified analogs of sulfoquinovosyl acylglycerol (SQAG) present in sea algae, have been synthesized and it has been observed that they selectively accumulate in tumor cells and prevent the development of tumor cell. 63 Alternative to classical carbohydrate was recently reported by Zelenetskii. This is a complex among polysaccharide hyaluronic acid (HA) and polyborate with the most biochemically adaptive and aqueous-stable structure of 26.…”
Section: Boronated Carbohydratesmentioning
confidence: 99%
“…In addition, carbohydrates obtained by natural source could be used in future for synthesis of novel BNCT agents. The sulfoquinovosyl acylpropanediol (SQAP) 25a and 25b , the chemically modified analogs of sulfoquinovosyl acylglycerol (SQAG) present in sea algae, have been synthesized and it has been observed that they selectively accumulate in tumor cells and prevent the development of tumor cell 63 …”
Section: Debut Of the New Boron Agent Developed For Bnctmentioning
confidence: 99%
“…Sulfoquinovosyl acylglycerol (SQAG) 25 was isolated from sea algae and characterized by Sakaguchi et al, and 25 and its derivative sulfoquinovosyl acylpropanediol (SQAP) 26 were reported to be accumulated in cancer cells and exhibit weak toxicity against normal cells (Figure 13a) [33]. Because the modification of the long alkyl chain of SQAG has negligible effect on its biological activity, the design and synthesis of SQAP derivatives 27 and 28 containing a boron cluster unit and iodine atoms as BNCT agents and imaging agents for X-ray computed tomography (CT) were conducted [34,35].…”
Section: Design and Synthesis Of Boron-containing Sugars For Bnctmentioning
confidence: 99%
“…For the aforementioned purpose, we previously reported on the design and synthesis of sulfoquinovosyl acyl glycerol (SQAG) derivatives and 2-boryl-1,2-dideoxy- d -glucose derivatives, which were possibly transferred into cancer cells through the glucose transporter 1 (GLUT1), , because large amounts of d -glucose are consumed by anaerobic glycolysis during the rapid proliferation of cancer cells, which is known as the Warburg effect . However, their effect on BNCT was not satisfying, despite the moderate intracellular uptake of these agents.…”
Section: Introductionmentioning
confidence: 99%